FACTORS DRIVING CONSUMER PURCHASE DECISION IN SELECTING SMARTPHONE (Study: Students Of Faculty Of Economics And Business) - Soriton, Lavenia; Tumiwa, Johan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
A Smartphone is a mobile phone, generally built on with a mobile operating system that has more advance computing capability and connectivity than a feature phone. People use Smartphone less for the phone calls and more for internet browsing, social media, emails, online shopping, navigation and so many other things. Smartphone are replacing more of gadgets like digital cameras and alarm clocks. And now there has been an increasing in the number of Smartphone users in Manado. This research is aimed to analyze the factors driving buying decision in selecting smartphone for smartphone users using Factor Analysis for data reduction that summarizes the observed factors. The population refers to students of Faculty of Economics and Business with sample size as many as 110 respondents and convenience sampling used to as the sampling technique. The finding resulted there are twoÂ new factors formed from seven most dominant out of twenty variables, first factor which is Performance Expectancy divided by five items those are Technology Factors, Usability Features, Perceived Quality, Perceived Ease of Use and Brand Loyalty and second factor which is Personal Factors divided by two items those are Product Sacrifice and Consumer Attitude. The recommendations that can be drawn in this research, is the smartphone company should be able to improve the quality of its product in order to meet the customers need. Keywords: consumer purchase decision, analysis factor, smartphone